0265 Sleep Variables and Somatic Symptoms as Correlates of Marijuana Use In A Nationally Representative Sample Of Adolescents. (27th April 2018) - Sita, K R; Luk, J W; Haynie, D L; Lewin, D; Simons-Morton, B G
Abstract: Introduction: Marijuana is the most commonly used recreational drug in the US. Some adolescents use marijuana to improve sleep problems and/or relieve somatic symptoms. Few studies have considered associations of both sleep variables and somatic symptoms with marijuana use. We examined sleep problems (trouble falling asleep, trouble staying asleep), duration (scheduled-days and weekends) and timing (chronotype and social jetlag) in relation to past year marijuana use. Further, we tested whether these associations were independent somatic symptoms. Methods: Data were drawn from a nationally representative sample of 12 th grade adolescents in the NEXT Generation Health Study ( n =1, 659). Logistic regressions were used to estimate the odds of any past year marijuana usage to sleep behaviors. For each sleep variable, the final model adjusted for demographics (sex, race/ethnicity, family affluence, parent education, and family structure), somatic symptoms (an index of headache, stomachache, backache, and feeling dizzy), and complex survey design. Results: Somatic symptoms were associated with marijuana use across all models. Over-and-above the effects of somatic symptoms, sleep timing (chronotype, AOR=1.52, 95%CI=1.25–1.84; social jetlag, AOR=1.43, 95%CI=1.20–1.71) and trouble falling asleep (AOR=1.47, 95%CI=1.06–2.05) were associated with marijuana use. Trouble staying asleep (AOR=1.32, 95%CI=0.90–1.92) was not associated with marijuana usage independent of somatic symptoms. Sleep duration showed no associations with marijuana use. Conclusion: While aspects of sleep, such as timing, are independently associated with marijuana use, other variables, such as trouble staying asleep may share an effect with somatic symptoms. With increasing availability of marijuana, this study highlights the need for understanding adolescents' motives behind using marijuana to self-medicate. Further research is needed to understand the complex inter-relationship between marijuana, sleep, and somatic symptoms overtime. Support (If Any): This project (contract HHSN275201200001I) was supported by the Intramural Research Program of the Eunice Kennedy Shriver National Institute of Child Health and Human Development; the National Heart, Lung, and Blood Institute; the National Institute on Alcohol Abuse and Alcoholism; the National Institute on Drug Abuse; and the Maternal and Child Health Bureau of the Health Resources and Services Administration.